Ajaran Sosio-Teologi dalam Kitab Nūr al-Ẓalām Sharḥ ‘Aqīdah al-‘Awwām Karya Syaikh Nawawi al-Bantanī (1813-1898 M.) - Muhammad, M. Khoirul Huda; Ayatullah, Ayatullah; Maria, Maria Ulfa Anshor (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This article aims to capture the socio-theological dimension in the book of ushuluddin Nusantara in the 19th century. The primary source of this research is the book Nūr al-Ẓalām Sharḥ 'Aqīdah al-'Awwām by Nawawi al-Bantanī (1813-1898 A.D.). With the hermeneutics of objectivism subjectivism, the researcher explored the contextual interpretation process of Nawawi al-Bantanī. The results of this study show that Nūr al-Ẓalām Sharḥ 'Aqīdah al-'Awwām is an annotation of the book 'Aqīdah al-'Awwām by Ahmad al-Marzūqī (d. 1864 A.D.). In annotating, Nawawi al-Bantanī does not only emphasize the textual meaning of the book of matan which reflects the views and horizons of its author. Nawawi al-Bantanī also developed his own horizons. For example, in his lecture on the word